Religious Literacy as Religion Literacy: A Response from the UK - Robertson, David G. (Method & theory in the study of religion, 2022)
This response builds on Wolfart’s observations on the theological underpinnings of the “religious literacy” paradigm in a North American context by reflecting on the situation in the United Kingdom. Here, it is even more apparent that institutional factors are a bigger driver than methodological factors, driven by the neo-liberalisation of the universities and the entrenched institutional dominance of confessional approaches to the study of religion. Yet it also provides a way for social-scientific scholars of religion to explain the instrumental value of the subject to policymakers and funding bodies. I conclude by sketching an approach to religious literacy more in keeping with post-phenomenological Religious Studies.